Pengujian Integrasi Pasar Modal di Kawasan Asia Sebelum dan Selama Pandemi Covid-19 - Anisha Cahyaningrum; Robiyanto Robiyanto (Jurnal Akuntansi Keuangan dan Bisnis, 2021)
The occurrence of the Covid-19 pandemic has caused a slowdown in a country's economy, creating new global risks. This can affect the world's capital markets. Previous research has discussed a lot about capital market integration. The current condition of the Covid-19 pandemic has shaken the world's capital markets, but there has been no research on capital market integration related to this condition. So it is necessary to research capital market integration before and during Covid-19. The analytical tool used in this research is OGARCH (Orthogonal Generalized Autoregressive Conditional Heteroscedasticity) to determine the degree of integration. The data used in this study are daily closing data for HSI, Nikkei 225, Nifty 50, STI, SSEC, and IHSG during the period before the Covid-19 pandemic (September-December 2019), and the period during the Covid-19 pandemic (March-June 2020). After conducting the research, it was found that the capital market understudy was not fully integrated in the two periods. This study also found that the JCI became more segmented during the Covid-19 pandemic after the Nifty 50 which was always segmented in both periods.